2015
DOI: 10.1016/j.childyouth.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

It's not as simple as it sounds: Problems and solutions in accessing and using administrative child welfare data for evaluating the impact of early childhood interventions

Abstract: In recent years, there has been increasing interest in using administrative data collected by state child welfare agencies as a source of information for research and evaluation. The challenges of obtaining access to and using these data, however, have not been well documented. This study describes the processes used to access child welfare records in six different states and the approach to combining and using the information gathered to evaluate the impact of the Early Head Start program on children's involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Numerous problems exist in using child welfare administrative data sets to address research questions about the effectiveness of intervention programs (Chaffin et al, 2012; Chamberlain et al, 2016; Green et al, 2015, Lucenko et al, 2015). For example, official records may misrepresent the actual incidence of abuse and neglect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous problems exist in using child welfare administrative data sets to address research questions about the effectiveness of intervention programs (Chaffin et al, 2012; Chamberlain et al, 2016; Green et al, 2015, Lucenko et al, 2015). For example, official records may misrepresent the actual incidence of abuse and neglect.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations (e.g., Chaffin, Hecht, Bard, Silovsky, & Beasley, 2012; Chamberlain, Feldman, Wulczyn, Saldana, & Forgatch, 2016; Green et al 2015) have identified a number of pitfalls concerning the use of child welfare administrative sets. We have attempted to address these concerns in this report.…”
Section: Introductionmentioning
confidence: 99%
“…This step is clearly essential to the process, yet can prove more convoluted than expected. What follows is a brief description of the major steps taken and lessons learned, as a more in-depth review of this process is available through Green et al (2015).…”
Section: The Spark Projectmentioning
confidence: 99%
“…Further, these files include the conclusions of these hotline calls, specifying whether a given report was investigated and if the allegation was ultimately substantiated. Previous research has supported the use of case file data and demonstrated the level of rigor that can be achieved in studies that utilize such records (Brownell & Jutte, 2013; Green et al, 2015). One argument that has been made is that case file records are not subject to the social desirability bias likely to be present in self-report of parenting behaviors (MacMillan, Jamieson, & Walsh, 2003), nor are they affected by forgetting, misremembering, or failure to disclose, all of which may be present in child self-report (Greenhoot, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation